ON THE ISSUE OF IMPLEMENTATION OF PROJECTS ON THE DEVELOPMENT AND PRACTICAL APPLICATION OF KNOWLEDGE IN THE DIGITAL ECONOMY (Scientific journal of the Fergana State University, 2024)
Higher education today faces important tasks, such as educating and training the younger generation, capable of actively participating in a qualitatively new, rapidly changing stage of development of society, as well as the implementation of priority projects to prepare students for the mastery and practical application of acquired knowledge in the digital economy. The article discusses the need to further improve the education system in the context of socio-political modernization of society.